PERAMALAN TINGKAT PENGANGGURAN TERBUKA PROVINSI BANTEN DENGAN METODE TRIPLE EXPONENTIAL SMOOTHING - Rindang Ndaru Puspita (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The Unemployment Rate is the main indicator to measure the unemployment in the labor force. The higher Unemployment Rate will have an impact on the decline in people's welfare. Based the results of SAKERNAS in February 2022, Banten Province's Unemployment Rate is the highest in Indonesia, besides that, since the Covid-19 pandemic, the Banten Province's Unemployment Rate has increased. There needs an effort to reduce the Unemployment Rate so that it can reduce the number of unemployed, one of which is by knowing the predicted value of the Unemployment Rate in the future. From the results of historical data analysis, it is known that the data pattern of the Banten Province's Unemployment Rate is seasonal, so the Triple Exponential Smoothing Method is suitable to be used because it can stabilize seasonal patterns. Forecasting is carried out to determine the Unemployment Rate in Banten Province in the next 7 periods, from Semester 2 of 2022 to Semester 2 of 2025. From the forecasting results, the MAPE value is 8.858859%, which is smaller than 10%, that  shows very accurate predictions. Furthermore, the results of this research  are expected to be used as consideration in determining strategies to reduce the Banten Province's Unemployment Rate